Los estudios de dinámica fluvial en cauces meandriformes: estado de la cuestión - Ollero Ojeda, Alfredo (Geographicalia, 2017)
This Department of Geography has started a line of research in the field of fluvial dynamics (OLLERO, 1989; Ebro river meandering valley) which has led to the achievement of un exhaustive bibliography. In this paper, un accont of the process is exposed in detail, giving un appraisal about the recent evolution of this scarcely cultivated in our country branch of Geomorphology, as well as its present-day tendencies.